2022
DOI: 10.1186/s40594-021-00324-w
|View full text |Cite
|
Sign up to set email alerts
|

The influences of social agents in completing a STEM degree: an examination of female graduates of selective science high schools

Abstract: Background Women are underrepresented in science, technology, engineering, and mathematics (STEM) professions. Even the most promising female students’ interest in STEM subjects often decreases during secondary school. Using the framework of the Social Cognitive Career Theory, the present study examined the influences of social agents in female students’ persistence in STEM. Specifically, the present study used a retrospective survey investigating the influence of parental education, teachers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 101 publications
0
11
1
6
Order By: Relevance
“…b. Environmental factors such as (a) students' research experience [22]; (b) if the students had a mentor or a parent with a STEM career [18,23,24]; (c) the experience of supportive learning environments in the family or at school [24,25]; (d) a sense of belonging at school [26][27][28]; and (e) the development of intellectual capacity for STEM [21].…”
Section: Introductionmentioning
confidence: 99%
“…b. Environmental factors such as (a) students' research experience [22]; (b) if the students had a mentor or a parent with a STEM career [18,23,24]; (c) the experience of supportive learning environments in the family or at school [24,25]; (d) a sense of belonging at school [26][27][28]; and (e) the development of intellectual capacity for STEM [21].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to systematically examine whether successful participation in a mentoring program offered to girls enrolled in secondary education can positively influence real‐life STEM choices made years after participation. While studies have examined the impact of (online) mentoring on real‐life choices of STEM majors and careers, 32 they were either retrospective surveys that did not address formal (online) mentoring programs or were studies with adults 36,37 . Studies with students in secondary education have so far primarily examined the short‐term effectiveness of formal (online) mentoring programs (e.g., influences on STEM interests and elective intentions in STEM) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that mentors have an influence on mentees’ career choices in STEM (i.e., majoring in a STEM subject at university or entering a STEM profession). For example, in a retrospective survey of 1425 female graduates of selective science, high schools in the United States 32 found that having a teacher as a mentor during high school correlated with university STEM major choices and degrees in STEM. However, studies examining associations between participation in formal STEM mentoring programs during secondary education and later career choices are lacking 13,33 .…”
Section: Introductionmentioning
confidence: 99%
“…in höheren Klassen oder unterschiedlichen zu Messzeitpunkten zeigen können (Krapp und Prenzel 2011 ; Lee und Chen 2019 ; Luo et al. 2022 ; OECD 2016 ; Potvin und Hasni 2014 ; Sjøberg und Schreiner 2019 ; van Vorst und Aydogmus 2021 ).…”
Section: Diskussionunclassified